FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN DAN LOYALITAS PELANGGAN PADA INDUSTRI PAKAN TERNAK PT. DINASTY PS KABUPATEN BLITAR DALAM PERSPEKTIF PEMASARAN AGRIBISNIS (AGRI-MARKETING) - Yudha, Danang Ananda (Oryza : Jurnal Agribisnis dan Pertanian Berkelanjutan, 2023)
ABSTRACT Dinasty PS (Poultry Shop) is a company engaged in the field of animal husbandry, especially animal feed located in the Blitar district, where the sales are mostly poultry feed, medicines and livestock equipment. The chicken farming system in the Dinasty PS environment is still a type of community farm that only uses conventional and family-friendly maintenance systems, so it only relies on a belief system. The purpose of this study in general is to determine the factors that influence customer satisfaction and loyalty in the Animal Feed Industry of PT. Dinasty PS Blitar Regency is seen in the perspective of agri-marketing (Agri-Marketing) and To find out the most influential factor on customer satisfaction and loyalty in the animal feed industry Dinasty PS Blitar district in the perspective of agribusiness marketing (Agri-Marketing). The research method used in this study is to use linear regression analysis. Linear regression analysis is used to determine cause and effect with the dependent variable customer satisfaction (Y1) and customer loyalty (Y2) and marketing mix as the Independent variable (X). The results obtained after conducting the study are: 1) Based on the results of the analysis of the marketing mix variable on customer satisfaction has a positive and significant effect, this is based on the results of data analysis using SPSS 16 showing the value of t is greater than ttable (tcount = 4.929, ttable = 1.667) which means that the Marketing Mix is ​​able to have a positive and significant effect on customer satisfaction in the Dynasti PS animal feed industry in Blitar Regency. 2) Based on the results of the analysis of the marketing mix variable on customer loyalty has a positive and significant effect. This is based on the results of data analysis using SPSS 16 showing a tcount greater than ttable (tcount = 5.719, ttable = 1.667) which means that the marketing mix is ​​able to have a positive effect and significant to customer loyalty in the Dynasti PS animal feed industry in the Regency. 3) The factors that influence customer satisfaction and loyalty are found that the most influential factors are on the promotion, process and product side. Keyword: Marketing Mix, Customer Satisfaction, Customer Loyalty, Agri-Marketing